2005
DOI: 10.1016/j.ssc.2005.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Observation of magnetoelectric behavior at room temperature in Pb(FexTi1−x)O3

Abstract: The coexistence of ferroelectric and ferromagnetic properties at room temperature is very rarely observed. We have been successful in converting ferroelectric PbTiO 3 into a magnetoelectric material by partly substituting Fe at the Ti site. The Pb(Fe 1-x Ti x )O 3 system exhibits ferroelectric and ferromagnetic ordering at room temperature. Even more remarkably, our results demonstrate a coupling between the two order parameters. Hence it could be a futuristic material to provide cost effective and simple path… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
66
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(72 citation statements)
references
References 11 publications
5
66
1
Order By: Relevance
“…The pyrochlore phase at 700°C is due to a low sintering temperature, which diminishes on increasing the temperature to 1000°C. The similar impurity phase was also observed in Pb͑Fe Ti͒O 3 system by Palkar et al 15 The particle size was calculated from XRD peak broadening using Scherer's formula as in Eq. ͑1͒.…”
Section: Methodssupporting
confidence: 61%
See 1 more Smart Citation
“…The pyrochlore phase at 700°C is due to a low sintering temperature, which diminishes on increasing the temperature to 1000°C. The similar impurity phase was also observed in Pb͑Fe Ti͒O 3 system by Palkar et al 15 The particle size was calculated from XRD peak broadening using Scherer's formula as in Eq. ͑1͒.…”
Section: Methodssupporting
confidence: 61%
“…In recent years, a few studies have been carried out to investigate on multiferroic properties of Fe substituted PbTiO 3 system. Palkar et al 15 have first observed magnetoelectric properties in ferroelectric PbTiO 3 by partially substituting Ti with Fe. Ren et al 16 showed room temperature ferromagnetism in Fe doped PbTiO 3 nanocrystals prepared by hydrothermal method using polyethylene glycol as surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…This porosity may be created by PVA, when used as binder during pellet formation process. Compared with the results reported by Palkar et al 18 for Pb͑FeTi͒O 3 system, the present system of Sr-doped Pb͑Fe, Ti͒O 3 shows better spontaneous polarization. This improvement may be attributed to small particles, which can easily control crystalline structure, defects, oxygen vacancies, and stiochiometry.…”
contrasting
confidence: 72%
“…Unfortunately, most of the known multiferroic systems are antiferromegnetic with transition temperatures below room temperature [3,4]. Therefore, for device applications these materials hardly find any use.Recently, we have reported novel materials exhibiting magnetoelectric properties at room temperature [5][6][7]. In this letter we report room temperature multiferroic properties for lower compared to any of these phases.…”
mentioning
confidence: 76%